Assessment of Knowledge Attitude and Practice about ‘SADE’ among Dental Undergraduate Students - Likhitha, Dr. Y.; Pratap, Dr. K. V. N. R.; Madhavi Padma, Dr. T.; Kumar, Dr. Srujan; Singh, Dr. Surbhit; Soumya, Dr. V. (International Journal Of Drug Research And Dental Science, 2025)
Background: The dental setting can be a source of significant anxiety, particularly for individuals with sensory sensitivities, such as those with autism spectrum disorder (ASD) or sensory processing difficulties. Sensory Adapted Dental Environments (SADE) have been developed to reduce anxiety and improve patient cooperation by modifying environmental stimuli. Despite growing evidence supporting their effectiveness, little is known about the awareness and attitudes of undergraduate dental students toward SADE. Objective: This study aims to assess the knowledge, perception, and attitudes of undergraduate dental students regarding the implementation and importance of sensory-adapted dental environments in clinical practice. Methods: A cross-sectional survey was conducted among 201 undergraduate dental students from multiple academic years using a structured questionnaire. The survey assessed students’ awareness of SADE, their attitudes toward its effectiveness, and their willingness to apply such adaptations in future clinical settings. Descriptive statistics and comparative analyses were used to interpret the results. Results: While 72% of participants were unfamiliar with the concept of SADE prior to the study, 85% acknowledged its potential benefits after being introduced to its principles. Students expressed strong support for implementing sensory modifications to accommodate patients with special needs. However, many reported a lack of formal training or exposure to SADE practices during their education. Conclusion: There is a positive attitude among dental students toward the use of sensory-adapted environments, but a significant knowledge gap exists. Integrating SADE concepts into undergraduate dental curricula may enhance students’ preparedness to deliver inclusive, patient-centered care.